2018
DOI: 10.1007/s12652-018-0784-5
|View full text |Cite
|
Sign up to set email alerts
|

Q-Rapids framework for advanced data analysis to improve rapid software development

Abstract: The quality of software, in particular developed rapidly, is quite a challenge for businesses and IT-dependent societies. Therefore, the H2020 Q-Rapids project consortium develops processes and tools to meet this challenge and improve the quality of the software to meet end-users requirements and needs. In this paper, we focus on data analytics that helps software development companies evaluate the quality of the software. In fact, most software development teams use tools such as GitLab, SonarQube or JIRA (am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The Q-Rapids approach [16] is based on gathering and analysing data from several sources (software repositories, project management tools, system usage and quality of service) [20], [26]. Data is aggregated into quality indicators that are rendered to the different stakeholders by means of the Q-Rapids tool [25].…”
Section: B the Q-rapids Projectmentioning
confidence: 99%
“…The Q-Rapids approach [16] is based on gathering and analysing data from several sources (software repositories, project management tools, system usage and quality of service) [20], [26]. Data is aggregated into quality indicators that are rendered to the different stakeholders by means of the Q-Rapids tool [25].…”
Section: B the Q-rapids Projectmentioning
confidence: 99%
“…In our previous Q-Rapids related papers (Kozik et al 2017(Kozik et al , 2018, we showed the presented results of softwarerelated data analysis and correlation.…”
Section: Context and Related Workmentioning
confidence: 99%
“…While in the previous work we focused on the data gathering and processing it towards quality metrics, indicators and requirements generation [21] [7], we hereby target the prediction of the software related metrics.…”
Section: Introduction and Contextmentioning
confidence: 99%